PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PERMEN TOLAK ANGIN DI SEMARANG - Krestiawan Wibowo Santoso; Handoyo Djoko Waluyo; Sari Listyorini (Universitas Diponegoro, 2014)
Developmental needs of consumers who increasingly complex and competitive market led to a sharp decline Tolak Angin candy should be able to compete to demonstrate its product superiority and seize the attention of consumers. consumers who will make a decision in choosing to consider various things before buying. Consideration, among others, influenced by the quality of the product, pricing, and promotions are determined by the company. Formulation of the problem in this paper is the sales during 2007 to 2012 has fluctuated. The type of research uses explanatory research approach with the method of data collection using interview and data collections devices using a questionnaire with a sample of 100 respondents in village Tembalang Semarang using purposive sampling method (sampling technique is based on certain conditions). Analysis technique used validity, reliability testing, simple linear regression, multiple linear resgression, t test, and F test with the aid of SPSS 20.0. Based on a statistical calculation with linear regression analysis can be shown by the regression equation Y = 10,521 + 0,169 X1 + 0,072 X2 + 0,193 X3 from the regression equation is known that the product quality, pricing, and promotion have a positive impact on purchasing decisions. Results of calculation of the coefficient of determination 0,276 magnitude. This suggests that product quality, pricing, and promotion can explain purchasing decision by 27,6%. While the remaining 72,4% is explained by other variable that are not observed. Based on the data analysis we can conclude the existence of a positive effect of product quality, pricing, and promotion on purchasing decisions have a strong level of closeness of relationship this means that if the product quality, pricing, and promotion will lead to higher purchasing decisions.